Integrated Transcriptome Profiling Revealed That Elevated Long Non-Coding RNA-AC007278.2 Expression Repressed CCR7 Transcription in Systemic Lupus Erythematosus - You, Yi; Zhao, Xingwang; Wu, Yaguang; Mao, Jiangming; Ge, Lan; Guo, Junkai; Zhao, Chenglei; Chen, Dong; Song, Zhiqiang (Frontiers in Immunology, 2021)
Purpose: Systemic lupus erythematosus (SLE) is a serious autoimmune disease. Its molecular pathogenesis, especially the long non-coding RNA (lncRNA) function, remains unclear. We want to investigate the lncRNA dysregulation profile and their molecular mechanisms in SLE. Methods: In this study, we analyzed the transcriptome profiles (RNA-seq) of peripheral blood mononuclear cells (PBMCs) from SLE patients and two published transcriptome datasets to explore lncRNA profiles. The differentially expressed lncRNAs were confirmed by quantitative real-time PCR in another set of female patients. We constructed the lncRNA-mRNA regulatory networks by performing weighted gene co-expression network analysis (WGCNA). Dysregulated lncRNA AC007278.2 was repressed by short hairpin RNA (shRNA) in Jurkat cells. Dual-luciferase reporter gene assay was performed to investigate the regulatory mechanism of AC007278.2 on target gene CCR7. Results: We observed dominant up-regulation of transcripts, including mRNAs and lncRNAs, in SLE patients. By WGCNA method, we identified three modules that were highly related to SLE. We then focused on one lncRNA, AC007278.2, with a T-helper 1 lineage-specific expression pattern. We observed consistently higher AC007278.2 expression in SLE patients. Co-expression network revealed that AC007278.2 participated in the innate immune response and inflammatory bowel disease pathways. By knocking down AC007278.2 expression, we found that AC007278.2 could regulate the expression of inflammatory and cytokine stimulus response-related genes, including CCR7, AZU1, and TNIP3. AC007278.2 inhibits the functional CCR7 promoter to repress its transcription, thereby regulating autoimmunity and follicular T-helper cell differentiation. Conclusion: In summary, our study indicated the important regulatory role of lncRNAs in SLE. AC007278.2 may be treated as a novel biomarker for SLE diagnosis and treatment.